RepoMMan Systems Documentation - Lamb, Simon W (The University of Hull)
The purpose of this document is give an overview of the RepoMMan tool and the architecture upon which it is built. The RepoMMan architecture is made up of several layers. These layers include the Adobe Flex Presentation layer, BPEL Processes, and the RepoMMan and Fedora Web Services that they call. The document will also cover the Java servlets that have been written to provide functionality that services could not provide.